Racism and mental health : prejudice and suffering - Bhui, Kamaldeep (Jessica Kingsley Publishers, 2002)
This thought-provoking book investigates the impact of racism (both conscious and unconscious) in mental health settings, covering individual clinical encounters and the broader picture of service provision. The authors offer insights into manifestations of racism in contemporary Britain; racial and cultural identity and the significance of these in psychotherapy; and the inequalities in provision of mental health services to minority ethnic communities. They consider the problems of racism and mental health, not in isolation but in the larger context of cultural difference and social inequali.